Protective Effect against Hydroxyl-induced DNA Damage and Antioxidant Activity of Citri reticulatae Pericarpium - Dongfeng Chen; Yanping Huang; Xican Li (Tabriz University of Medical Sciences, 2013)
Purpose: As a typical Chinese herbal medicine, Citri reticulatae pericarpium (CRP) possesses various pharmacological effects involved in antioxidant ability. However, its antioxidant effects have not been reported yet. The objective of this work was to investigate its antioxidant ability, then further discuss the antioxidant mechanism. Methods: CRP was extracted by ethanol to obtain ethanol extract of Citri reticulatae pericarpium (ECRP). ECRP was then measured by various antioxidant methods, including DNA damage assay, DPPH assay, ABTS assay, Fe3+-reducing assay and Cu2+-reducing assay. Finally, the content of total flavonoids was analyzed by spectrophotometric method. Results: Our results revealed that ECRP could effectively protect against hydroxyl-induced DNA damage (IC50 944.47±147.74 μg/mL). In addition, it could also scavenge DPPH· radical (IC50349.67±1.91 μg/mL) and ABTS+• radical (IC5011.33±0.10 μg/mL), reduce Fe3+ (IC50 140.95±2.15 μg/mL) and Cu2+ (IC50 70.46±1.77 μg/mL). Chemical analysis demonstrated that the content of total flavonoids in ECRP was 198.29±12.24 mg quercetin/g. Conclusion: Citri reticulatae pericarpium can effectively protect against hydroxyl-induced DNA damage. One mechanism of protective effect may be radical-scavenging which is via donating hydrogen atom (H·), donating electron (e). Its antioxidant ability can be mainly attributed to the flavonoids, especially hesperidin and narirutin.